The Embattled Conflict over Freedom of Speech through Political Cartoons in Europe: From the Danish Cartoons to the Russian Cartoons - BOUTI, Rachida; Hocine, Aicha (Faculty of Letters and Foreign Languages Department of English, 2023)
Freedom of speech through political cartoons has thoroughly been mediated through the last decades in Britain and European countries. As a matter of fact, some controversial political cartoons have led to debate over freedom of speech and its limitations. The study aimed to shed light on how much political cartoon freedom of expression might be tolerated in a multicultural society like that of Britain and the majority of European nations, especially after the tremendous aftermaths of some political cartoons that have been published and republished in the European continent. It aimed at investigating issue of unlimited free speech and the humoristic feature of political cartoons. Thus, analytical and comparative approaches have been exploited to find out the reasons that have made free speech through political cartoons questionable. Online sources that can be trusted, including scholarly publications, novels, newspaper articles, and websites, have been used. Accordingly, the study has been conducted through three stages: Diving through the origins of free speech, the nature of political cartoons, then analyzing and comparing a few cartoons. It was argued that free speech through political cartoons was an embattled area where both a limitless free speech and a satirical nature of political cartoons proliferated mixed reactions towards some political cartoons. Those reactions were subject to constant research